Characterization of pathogenic roles of two Erysipelothrix rhusiopathiae surface proteins. (January 2018) - Zhu, Weifeng; Cai, Chengzhi; Huang, Jingjing; Liu, Liang; Xu, Zhongmin; Sun, Xiaomei; Jin, Meilin
Abstract: Erysipelothrix rhusiopathiae is the causative agent of animal erysipelas and human erysipeloid. E. rhusiopathiae HP0728 and HP1472 have been reported to be down regulated in low-virulence or avirulent strains, but their pathogenic roles are not known. In this study, it was found that E. rhusiopathiae HP0728 and HP1472 were displayed on the surface of E. rhusiopathiae . Moreover, recombinant HP1472 could adhere to pig vascular endothelial cells. Recombinant HP0728 could bind host plasminogen but could not bind fibronectin. In conclusion, our work suggested that HP0728 and HP1472 are virulence factors of E. rhusiopathiae . Highlights: Erysipelothrix rhusiopathiae is the causative agent of animal erysipelas and human erysipeloid. There are binding activities of HP0728 to host plasminogen and HP14472 to host endothelial cells. Our work suggested that HP0728 and HP1472 are candidate virulence factors of E. rhusiopathiae.